ON THE QUESTION OF PROSPECTS OF LIBRARY INFORMATION SYSTEMS DEVELOPMENT IN CONDITIONS OF GLOBAL CRISIS - Kosolapov, Anatoliy A.; Motin, Oleksandr V.; Loskutov, Dmytro V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The report focuses on analysis of library information systems, prospects of their development in conditions of global crisis, also focuses on ―cloud computing‖ and formation of common library information ―cloud‖.